(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Dobbs v. Jackson marks an Overruling in Supreme Court jurisprudence of historic significance. By denying constitutional relevance to the right to abortion, the Court restores an orginalist reading of the US Constitution and selectively operates on the subject of civil rights, arguably ushering in a season that could have repercussions for reproductive rights and women’s freedom to exercise control over their own choices. The qualification of abortion, which had been consolidated with Roe v. Wade and later with Planned Parenthood v. Casey, had been far from without weaknesses. Both the Court’s dissenting opinions and legal doctrine had addressed these aspects, focusing on the Penumbra of the Fourteenth Amendment of the US Constitution, reflecting on the appropriateness of anchoring abortion to the equality clause offered by the Thirteenth Amendment, and focusing on the limits of a construction based on the public/private dichotomy. Fifty years of unresolved issues, of which this essay attempts to summarise the main issues.